Dynamic mechanical behaviour of Poly Ethylene Glycol Plasticized Polylacticacid - Kaiser, Mohammad Rejaul; Anuar, Hazleen; Abd. Razak, Shamsul (Trans Tech Publications, Switzerland, 2012)
Polylacticacid (PLA), produced from annually renewable, natural resources is a potential candidate for the partial replacement of petroleum based polymers and also for its biodegradability. PLA is well known for its better mechanical, thermal property but unfortunately the brittleness and rigidity limit its applicability. For a great number of applications such as packaging, fibers, films, etc., it is of high interest to formulate new PLA grades with improved flexibility and better impact properties. In order to develop PLA-based biodegradable packaging, the physico-mechanical properties of commercially available PLA should be modified using plasticizers. For this, PLA was melt-mixed with poly ethylene glycol (PEG) of 600 molecular weights by twin screw extruder. The thermal properties of plasticized PLA were characterized by utilization of dynamic mechanical analysis. The result shows that with addition of plasticizer glass transition temperature (Tg) isb decreased sharply and the storage modulus was also decreased.